2020
DOI: 10.3390/app10030784
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Horizontal Axis Deviation of a Small Radius TBM Tunnel Based on Winkler Foundation Model

Abstract: During the construction stage of the small radius TBM (tunnel boring machine) interval, the improper control of the boring parameters and the boring posture can cause the horizontal axis deviation of the shield tunnel. In order to address this issue, the TBM segments lining structure of the small radius interval is simplified as the continuous circular curved beam based on the longitudinal equivalent continuous model and Winkler elastic foundation beam theory. The theoretical model is solved through the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Another interesting group of papers dealing with soil properties and structures-soil interaction phenomena further extends the research fields covered in this Special Issue. In particular, [14] deals with the determination of Young modulus in bored piles, while [15] presents an investigation on the horizontal axis deviation of a small radius Tunnel Boring Machine (TBM). In this context, it is important to also mention the study in [16], and reporting on the friction resistance for slurry pipe jacking.…”
Section: Contentsmentioning
confidence: 99%
“…Another interesting group of papers dealing with soil properties and structures-soil interaction phenomena further extends the research fields covered in this Special Issue. In particular, [14] deals with the determination of Young modulus in bored piles, while [15] presents an investigation on the horizontal axis deviation of a small radius Tunnel Boring Machine (TBM). In this context, it is important to also mention the study in [16], and reporting on the friction resistance for slurry pipe jacking.…”
Section: Contentsmentioning
confidence: 99%
“…The principles of straight-line tunnel excavation inducing deformation of adjacent ground and pre-existing structures are fairly well established and further influence the field of small curvature tunnels. So far, the methods, used in predicting the ground movement, stress and response of adjacent structures due to shield tunneling along small radius curved route, are classified into three categories, including numerical simulations [14,21,30,45,48,52,55,51], on-site monitoring methods [7,39,52,58], and analytical methods [5,7,14,22,23,40]. In numerical simulation applications and researches, Zhang et al [55] suggested that inclined excavation loading could have an effect on the structural response and surface settlement produced by shield tunnels with different curvature radii.…”
Section: Introductionmentioning
confidence: 99%
“…Attitude control during TBM excavation is an important task for the TBM operator, and the degree of consistency between the excavation and design routes determines the construction quality of the tunnel (Marcher et al, 2022). Therefore, the intelligent guidance of TBM excavation is gaining popularity as a research topic, which mainly considers the following three aspects: modelling (Qiao et al, 2020), automatic control (Huang et al, 2022), and intelligent control of the tunnelling posture (Zhang and Ma, 2018;Garcia et al, 2021) A reliable design of tunnel support systems and the reasonable selection of support timing are important prerequisites to ensure the safety and long-term stability of tunnel construction (Farrokh et al, 2011;Kampas et al, 2020). Research regarding the intelligent support of tunnels includes the following three aspects: intelligent matching and optimisation of support parameters (Meschke et al, 2011), intelligent decisionmaking of supporting timing (Sun et al, 2007), and intelligent support structure (Liu et al, 2022c).…”
Section: Introductionmentioning
confidence: 99%